Digital-Based Literary Appreciation Teaching Materials to Strengthen Students' Communicative and Collaborative Character - Ida Ayu Made Wedasuwari; I Nyoman Adi Susrawan; I Komang Widana Putra; Ni Nyoman Ayu Tri Laksmi; Ni Luh Eka Purnami Pinatih (Jurnal Pendidikan Indonesia, 2024)
Using digital-based teaching materials is urgently needed to increase student involvement and foster communicative and collaborative character. However, many traditional teaching materials have yet to utilize the full potential of digital technology. This research aims to develop teaching materials for digital-based literary appreciation to strengthen students' communicative and collaborative character. This research method uses a qualitative descriptive method. The research design used in this research is 4-D Research and Development research. The development of digital-based literary appreciation teaching materials to strengthen students' communicative and collaborative character is carried out in several stages: analysis, design, development, implementation, and evaluation. Product trials are conducted on students based on the pretest and posttest results. The pretest results for students obtained data (quite effective) and posttest results (very effective) in learning literature to strengthen communicative and collaborative characteristics. Product trials were also carried out on lecturer groups to show good results and were suitable for use in literature learning. This research has implications for literature learning, especially in developing literary appreciation teaching materials combined with (digital) technological advances.